Bacteria and viruses - Thomas, Peggy 1960-; Gale Group (San Diego, California Lucent Books, 2004)
Discusses various types of bacteria and viruses, methods of fighting diseases, and how bacteria and viruses can be used to benefit people and the environment.
Swimming in a sea of microbes -- We are surrounded -- Early discoveries -- Fighting an invisible enemy -- Emerging microbes -- Harnessing invisible power -- Our future under a microscope.
Electronic reproduction.
Keywords: Bacteria -- Juvenile literature; Viruses -- Juvenile literature; Electronic books